A Smart System for Segregating Solid Waste using Machine Learning Model - Ihtifazhuddin, Cahyo; Muhammad Reza, Aditya (Multidisciplinary Applied Research and Innovation, 2023)
Waste management has problems consisting of the large quantity, variety of waste produced and the nature of the material is very complex and complicated. Recycling is one of the most typical approaches that can be taken. The proposed model involves Convolutional Neural Network (CNN), utilizing YOLO for object detection, and ORB for object tracking. This system can solve problems on a large scale such as districts hence the management becomes centralized and cost-effective. There will be more waste that can be recycled and benefit society. The future framework will have a complete system to become a complete garbage group for reuse, reduce, recycle (3R) use.